Analysis of Job Satisfaction, Employee Engagement and Turnover Intention at Millenia Embroidery - Datischa, Ulva; Ghazali, Achmad (The Indonesian Journal of Business Administration, 2014)
Abstract. Millenia Embroidery is a company in the form of small medium enterprises (SMEs) that operates in computer embroidery services. The company receives computer embroidery services both from individuals and organizations such as garment companies, footwear companies, etc. The company has been running the business since 1993. Nowadays, there are many new players in computer embroidery industry and the company found a difficulty in retaining their employees. There were many employees joined and left within a short term so that the employee turnover rate high. This negatively impacts on the productivity of company. Therefore, the company needs a solution and improvement to retain their employees. The author conducted a field study in the form of observations, interviews with company representatives, as well as documentation of company data. Next, the author conducted an employee survey with the approach of job satisfaction and employee engagement as the concept, as well as turnover intention. These two concepts were chosen as the approach because based on previous researches frequently found that job satisfaction and employee engagement have a relationship with employees’ intention to leave the company. Result of the study revealed that the root cause of employees’ job dissatisfaction at Millenia Embroidery due to factors of employee relationship with management, compensation and benefit, and work environment. While the root cause of employee disengagement due to factors of engagement opinions, engagement behaviors, and conditions for engagement. After knowing the causes of employee dissatisfaction and disengagement in the company, the author proposed an improvement recommendation in the form of solution based on issues that have been found and implementation plan of job satisfaction and employee engagement improvement that suit company condition. Key word: Job Satisfaction, Employee Engagement, Turnover Intention